PHYSICAL EXHAUSTION OF FUTURE DOCTORS - Jo’razoda Faxriddin Muhayddin o’g’li (Sciental Journals Publishing, 2025)
This article examines the importance of physical training for medical students. The methods and materials of the study, including literature analysis, surveys, observations, and experiments, are described. The study results indicate the necessity of modernizing the physical education system in medical schools to improve professional training and overall student health.
Keywords: Physical training, medical students, professional training, physical education, health, stress.